2017
DOI: 10.1002/smll.201703102
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Controlled 3D Periodic Metal Nanostructures Fabricated via Nanowelding

Abstract: A novel method for fabricating 3D metallic nanostructures to be used in polarized color filters based on nanoimprint lithography, electron-beam evaporation, and nanowelding is proposed. The shape of the nanostructures can be controlled by adjusting the temperature for the nanowelding process. Ag nanowires deposited on polymer patterns are accumulated by the nanowelding process to build up diverse 3D nanostructures. The morphologies of the fabricated 3D nanostructures are analyzed using scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…Advantageously, the proposed method allows transfer to be conducted at low temperature that is independent of the employed material. In our previous works, we found that Au, Al, and Ag nanostructures can be melted and oxidized below 150 °C, , which highlights the importance of performing transfer at low temperature. Consequently, we selected PMMA as a flexible substrate with a low T g and used DSC analysis to show that the T g of the PMMA film with the thickness of 150 μm (Figure a).…”
Section: Resultsmentioning
confidence: 85%
“…Advantageously, the proposed method allows transfer to be conducted at low temperature that is independent of the employed material. In our previous works, we found that Au, Al, and Ag nanostructures can be melted and oxidized below 150 °C, , which highlights the importance of performing transfer at low temperature. Consequently, we selected PMMA as a flexible substrate with a low T g and used DSC analysis to show that the T g of the PMMA film with the thickness of 150 μm (Figure a).…”
Section: Resultsmentioning
confidence: 85%
“…The junction of the second and third Au layer can be observed in the HRTEM images (see Figure S4b-(3 and 4)). In previous studies, 3D metal nanostructures were developed via nanowelding technology. , However, the polymer mold had to be fabricated on PET or PMMA substrates using nanoimprinting resin. Therefore, defects could appear in the 3D metal nanostructures while fabricating the multilayer nanostructures due to repeated heating, and the bottom metal layer could be damaged.…”
Section: Resultsmentioning
confidence: 99%
“…Nanowelding, caused by nanoscale melting-point depression, allows stacking at low temperatures in the range of 90−120 °C. 24 Figure 2h shows an SEM image of a sample transferred onto a 2″ diameter HA film. Additional SEM images obtained at five different points on the patterned HA film reveal the uniformity of the entire area (Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%